Trends Of Children’s Experiences With Nature And Their Connectedness To Nature - Mustapa, Nor Diyana (2018)
Connectedness to nature (CTN) during childhood plays an important role to influence children‟s attitudes and behaviour towards nature as a child now and later as an adult. The most significant factor that contributes to children‟s CTN is their experiences with nature, especially direct experiences. However, rapid urbanization, modernization, parental restrictions, and quality of the outdoor environment have reduced children‟s direct experiences with nature. Children obtain nature experiences mostly through indirect experiences, which may not have the same quality as direct experiences.